Determinação voltamétrica de zinco, cádmio, chumbo, cobre, selênio e manganês em ovos de galinha - Wiethan, Bruna Avila (2014)
The quality of the food deserves great attention due to its the influence on human nutrition and health. Food is the primary source of essential elements for humans, but also the main source of exposure to toxic elements. In this context, we developed a voltammetric method that allows the determination of zinc, cadmium, lead, copper, selenium and manganese in chicken eggs. This is because the eggs are among the most important and nutritious food in the daily diet, being routinely consumed by the population. Since the direct analysis of the array is impossible due to the high fat content of the sample were evaluated three different types of pre- treatment of same: acid digestion, digestion by UV irradiation and emulsion formation. The developed method allowed simultaneous and sequential determinations, speciation analysis, wide range linear for the analytes and low limits of detection and quantification. The average levels of concentration found in the samples were 10,54 mg kg-1 of Zn, 0.0074 mg kg-1 of Cd, 0.02 mg kg-1 of Pb, 3.78 mg kg-1 of Cu, 0,972 mg kg-1 of Se, and 0,530 mg kg-1 of Mn The accuracy of the method was evaluated through the analysis of certified reference material (SRM 8415 - Whole Egg Powder). Comparative measurements of the samples by atomic absorption spectrometry ( GF AAS ) technique commonly used for analysis of that sample, allowed verifying the equivalence of the methods.